Advances in Controllable Release Essential Oil Microcapsules and Their Promising Applications - Zhao, Yana; Wang, Yanbo; Zhang, Zhijun; Li, Huizhen (Molecules (Basel, Switzerland), 2023)
Essential oils (EOs) have emerged as natural and popular ingredients used in the preparation of safe and sustainable products because of their unique characteristics, such as antibacterial and antioxidant activity. However, due to their high volatility, poorly solubility in water, and susceptibility to degradation and oxidation, the application of EOs is greatly limited. One of the promising strategies for overcoming these restrictions is encapsulation, which involves in the entrapment of EOs inside biocompatible materials to utilize their controllable release and good bioavailability. In this review, the microencapsulation of the controllable release EOs and their applications are investigated. The focus is on the antimicrobial mechanism of various EOs on different bacteria and fungi, release mechanism of microencapsulated EOs, and preparation research progress of the controllable EOs microcapsules. In addition, their applications are introduced in relation to the food, textiles, agriculture, and medical fields.